Stressor yang Dihadapi Korban Bullying - Anak Agung Sagung Suari Dewi; Novianti Astaningtias, Ni Made Irene (Bali International University, 2022)
Background: Stress is a pressure that came from inside out of a person, and other problematic situations in life (Sarafino & Smith, 2012). Biological, chemical, or other outside stimulus that triggers the stress can be defined as stressor, and bullying is one of them. Researcher is having an assumption that bullying gives many negative effects for adolescence. Purpose: This research aims to get a description about stressors that must be faced by bullying victim. Method: This research uses qualitative method with case study design. Certain phenomena that will be discussed in this research is adolescence’s psychological perception about stressor that came from bullying. Result: There are 3 participants, who have been asked about bullying that has ever happened to them. Bullying is a serious stressor for an unhealthy mental state, because bullying kept happening to the victims, even the problems have been solved, and they have no wrong-doing to the suspects. All participants have negative affects while being bullied, such as anger, upset, fear, crying a lot, and have difficulties in sleeping. Conclusion: According to this research, being bullied verbally and physically overtime, even they have no wrong-doing to the suspects, have been stressors to the victims.